Positive effects of the catastrophic Hurricane Patricia on insect communities. Issue 1 (December 2018) - Novais, Samuel; Macedo-Reis, Luiz; Cristobal-Peréz, E. Jacob; Sánchez-Montoya, Gumersindo; Janda, Milan; Neves, Frederico; Quesada, Mauricio
Abstract Highly seasonal conditions of tropical dry forests determine the temporal patterns of insect abundance. However, density-independent factors such as natural disturbances can abruptly change environmental conditions, affecting insect populations. We address the effects of the Hurricane Patricia (category 5) on species density and abundance of three feeding guilds of herbivorous insects (sap-sucking, folivorous beetles and xylophagous) and predatory beetles associated to the canopy of a tropical dry forest. Hurricane Patricia has been the strongest tropical hurricane ever reported in the Western Hemisphere. Herbivorous insects (sap-sucking and xylophagous) and predatory beetles increased in species density and abundance in the following months after the hurricane, compared to samples before it. The positive response of sap-sucking insects to Hurricane Patricia was probably related to an increase in the availability of new shoots and leaf meristems after the natural coppicing by the hurricane, while xylophagous guild seems to have been positively affected by the increase in the amount and diversity of deadwood resources. The positive response of predatory beetles may be the result of a bottom-up effect due to a greater availability of arthropod preys after the hurricane. We demonstrated that catastrophic hurricane disturbances could be important events that temporarily increase the species density and abundance of insects in tropical dry forests.